Koncepcja "kary wiecznej" w eschatologii Wacława Hryniewicza - Raczyński-Rożek, Maciej 1981- (2019)
Wacław Hryniewicz znany jest w Polsce przede wszystkim z propagowania teologii nadziei powszechnego zbawienia. Kwestią, która od razu narzuca się czytelnikowi eschatologii lubelskiego teologa, jest pytanie o istnienie piekła czy też kary wiecznej. Rzeczywistość ta, obecna w nauczaniu Jezusa i przepowiadana przez wieki w Kościele, zdaje się negować istnienie nadziei opisywanej przez lubelskiego teologa. W odpowiedzi na tę wątpliwość w artykule zostały omówione najważniejsze argumenty teologiczno-spekulatywne, biblijne oraz egzystencjalne dotyczące rzeczywistości potępienia w eschatologii Wacława Hryniewicza. Podjęto także próbę krytycznego ustosunkowania się do nich.
Wacław Hryniewicz is known in Poland above all for propagating the theology of the hope of universal salvation. The issue that immediately imposed upon the reader of the eschatology of the theologian from Lublin, is the question of the existence of hell or eternal punishment. This reality, present in the teaching of Jesus and foretold in the Church for centuries, seems to contradict the existence of the hope described by Hryniewicz. In response to this doubt,the article discusses the most important theological, speculative, biblical and existential arguments regarding the reality of damnation in the eschatology of Wacław Hryniewicz. It also attempts at a critical examination of these arguments.
Wacław Hryniewicz is known in Poland above all for propagating the theology of the hope of universal salvation. The issue that immediately imposed upon the reader of the eschatology of the theologian from Lublin, is the question of the existence of hell or eternal punishment. This reality, present in the teaching of Jesus and foretold in the Church for centuries, seems to contradict the existence of the hope described by Hryniewicz. In response to this doubt, the article discusses the most important theological, speculative, biblical and existential arguments regarding the reality of damnation in the eschatology of Wacław Hryniewicz. It also attempts at a critical examination of these arguments.
Keywords: apokatastaza; nadzieja; kara wieczna; Hryniewicz; apokatastaza